Reviews - Katarzyna Marciniak, KM; Stefano Rozzi, SR; Panagiotes Kontonasios, PK; Alessandro Mandrino, AM (Ciceroniana On Line, 2021)
Christoph PIEPER, Bram VAN DER VELDEN (eds.), Reading Cicero’s Final Years: Receptions of the Post-Caesarian Works up to the Sixteenth Century. With Two Epilogues (K. MARCINIAK)